NUMERICAL MODELING OF AIR POLLUTION FROM DUMPS - Biliaiev, M. M.; Rusakova, T. I.; Kalashnikov, I. V.; Bondarenko, I. O.; Gunko, E. Y. (Science and Transport Progress, 2019)
Purpose. Rock dumps are long-term sources of air pollution. A significant amount of harmful substances enters the atmosphere. Particularly intense is the pollution of atmospheric air due to dusting dumps. An important task is the development of methods for predicting the dynamics of atmospheric air pollution during the emission of harmful impurities from dumps. When developing methods for predicting the dynamics of air pollution from dumps. It is very important to create a universal model that would allow on a single computing platform to calculate the process of atmospheric air pollution for various impurities that are released from dumps. Another important problem is the choice of the place for optimal placement of future dumps in order to minimize their negative impact on the environment. Methodology. Numerical modeling of the formation of atmospheric pollution zones near rock dumps is based on the application of the equation of turbulent dispersion of an impurity in the atmosphere. To solve the problem of choosing the rational location of the dumps, the conjugate equation is used. Numerical integration is carried out using an implicit difference scheme. Findings. Numerical models are developed. The first numerical model allows one to evaluate the effect of rock dumps on air pollution. The second numerical model allows, on the basis of a one-time calculation, to determine the rational location of the future dump from the point of view of its minimal impact on air pollution. Originality. Two numerical models are proposed that are based on the application of the turbulent diffusion equation and the conjugate equation. These models make it possible to quickly determine the effect of rock dumps on air pollution. The models take into account the convective transport of the pollutant, atmospheric turbulent diffusion, the intensity of the emission of impurities from the dump. Practical value. The developed numerical models are implemented in the form of program codes. These program codes can be used when performing serial calculations on computers of low and medium power, i.e. computer technology, which is available to organizations involved in environmental issues in technologically saturated regions. When carrying out calculations based on the constructed numerical models, typical initial data are used regarding the intensity of the emission of impurities from dumps, weather conditions characteristic of a specific region of the country.